Gonad maturity and spawning type of silurid catfishes, Ompok miostoma (Vaillant, 1902) from Mahakam watershed, East Kalimantan - Jusmaldi Jusmaldi; Dedy Duryadi Solihin; Ridwan Affandi; M F Rahardjo; Rudhy Gustiano (Jurnal Iktiologi Indonesia, 2017)
Silurid catfishes O. miostoma (Vaillant, 1902) is an endemic species in Mahakam Watershed East Kalimantan. Biology reproduction aspect of this species is not yet known. The purpose of this study was to determine the stages of gonad maturation characteristics, egg size, and spawning type. Fish sampling conducted monthly from November 2013 to Oc-tober 2014, using many gears at four locations in Mahakam Watershed, i.e: Semayang Lake, Belayan River, Siran River and Tering River. To determine the stages of gonad maturation in silurid catfishes were carried out by morphologic and histologic examination methods. Spawning fish type was determined based on the distribution of eggs diameter. The results of this research showed that there are five gonad maturation stages of males and females of silurid catfishes. Dis-tribution of eggs diameter in gonad maturity stages ranges from 0.54 – 1.30 mm with simultaneous spawning type. Abstrak Ikan lais O. miostoma (Vaillant 1902) adalah spesies ikan endemik di Daerah Aliran Sungai (DAS) Mahakam Kaliman-tan Timur. Aspek biologi reproduksi ikan ini belum pernah diketahui. Penelitian ini bertujuan untuk menentukan karak-teristik tahap kematangan gonad, ukuran telur, dan tipe pemijahan. Pengambilan contoh ikan dilakukan setiap bulan, dari bulan November 2013 sampai Oktober 2014 menggunakan berbagai jenis alat tangkap pada empat lokasi penelitian di DAS Mahakam yang meliputi: Danau Semayang, Sungai Belayan, Sungai Siran, dan Sungai Tering. Penentuan ting-kat kematangan gonad ikan lais dilakukan dengan metode pemeriksaan morfologis dan histologis. Tipe pemijahan ikan lais ditentukan berdasarkan sebaran diameter telur. Hasil penelitian menunjukkan ada lima tahap kematangan gonad jantan dan betina ikan lais. Sebaran diameter telur pada tahap matang gonad berkisar dari 0,54 - 1,30 mm dengan tipe pemijahan serempak.